2010
DOI: 10.1093/sleep/33.4.467
|View full text |Cite|
|
Sign up to set email alerts
|

Sex Differences in the Association of Regional Fat Distribution with the Severity of Obstructive Sleep Apnea

Abstract: Regional obesity is associated with obstructive sleep apnea severity, although differently in men and women. In women, a direct influence of neck fat on the upper airway patency is implicated. In men, abdominal obesity appears to be the predominant influence. The apnea-hypopnea index was best predicted by a combination of Dual Energy Absorptiometry-measured mass and traditional anthropometric measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
105
2
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(120 citation statements)
references
References 33 publications
4
105
2
9
Order By: Relevance
“…In addition, there is a relationship between obstructive sleep apnea and resistance to leptin, a hormone derived from adipose tissue that is important in weight control and energy expenditure (27) . Another important aspect, is that the SD generally have a higher prevalence in males (26) , However, we found no difference in the frequency distribution, besides the scales scores were also similar between the genders. The small number of male patients evaluated in the study (22%) may have been responsible for the result.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In addition, there is a relationship between obstructive sleep apnea and resistance to leptin, a hormone derived from adipose tissue that is important in weight control and energy expenditure (27) . Another important aspect, is that the SD generally have a higher prevalence in males (26) , However, we found no difference in the frequency distribution, besides the scales scores were also similar between the genders. The small number of male patients evaluated in the study (22%) may have been responsible for the result.…”
Section: Discussioncontrasting
confidence: 55%
“…The presence of central obesity increases the accumulation of visceral fat, causing instability or even collapse of the upper airways (25,26) . The obesity and the SD have congruent pathophysiology, one-night sleep deprivation significantly affects ghrelin and cortisol levels, favoring the reduction of energy expenditure and increasing the sensation of hunger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A radiologic imaging study as magnetic resonance showed the greater soft tissue loading on the airway in men [38]. However, other study, a dual energy X-ray absorptiometry, reported a direct influence of neck fat on upper airway patency in women [32]. A recent study in Turkey reported that NC was of greater value than waist circumference in men but not in women [23].…”
Section: Discussionmentioning
confidence: 98%
“…Была выяв-лена прямая связь между увеличением локального отложения жира вокруг глотки, окружающих мягких парафарингеальных тканях верхних дыхательных путей и степенью тяжести СОАГС [32]. Показано, что ожирение вокруг грудной клетки и живота вы-зывает снижение объема легких и сужение глотки, воздействуя на глоточную проходимость и разви-тие СОАГС [33]. Особое внимание как предиктору СОАГС уделяется распределению жира в области шеи [34].…”
unclassified